(untitled) - Sherman, Dennis; Dennis Sherman; Joyce Salisbury (New York)
Imagine your Western Civilization students evaluating evidence, making connections, and thinking analytically about the past and present. Imagine your students better understanding the development of western ideas and values and the impact on today’s world. WEST, a brief, lively narrative offers a rich, innovative and integrated teaching and learning program for today’s Western Civilization courses. One that combines an outstanding design and a ground-breaking digital program, Connect History, that embraces instructor’s course goals while meeting students where they learn best, in an active environment
Keywords: Civilization; Western; Civilization; Western